The stadium effect: rodent damage patterns in rice fields explored using giving‐up densities - Jones, Clare R.; Lorica, Renee P.; Villegas, James M.; Ramal, Angelee F.; Horgan, Finbarr G.; Singleton, Grant R.; Stuart, Alexander M. (Wiley, 2017)
Rodents are globally important pre‐harvest pests of rice. In Southeast Asia, rodent damage to growing rice crops is commonly concentrated towards the center of rice fields, away from the field edge, resulting in a clear pattern known as the “stadium effect.” To further understand this behavior of rodent pests and to develop recommendations for future research and management, we examined the relation between giving‐up densities (GUDs) and damage patterns. In Tanay, Luzon, Philippines, GUD trays containing pieces of coconut in a matrix of sand were placed at 4 different distances from the field edge to quantify the perceived risk of predation in a rice field pest, Rattus tanezumi. GUDs were recorded during a dry and wet season crop at the reproductive and ripening stages of rice. In addition, assessments of active burrows, tracking tile activity and rodent damage to the rice crop, were conducted in the dry season. GUDs were significantly lower in the center of the rice fields than on the field edges, suggesting that rodent damage to rice is greater in the middle of rice fields due to a lower perceived predation risk. Furthermore, this perception of predation risk (or fear) increases towards the field edge and was greatest on the rice bund, where there was no vegetation cover. We discuss the implications for rodent management and rodent damage assessments in rice fields. This is the first documented use of GUDs in a rice agro‐ecosystem in Asia; thus we identify the challenges and lessons learned through this process.